Desenvolvimento de um multímetro de bancada para medição em circuitos elétricos de baixa potência - SILVA, Tayana Lima da (2023)
In this work we present the development of a benchtop multimeter prototype for measuring and testing low-power electrical circuits. The motivation for developing the prototype emerged as a need to alleviate the lack of measuring instruments in the laboratory of electrical and electronic circuits at the Faculty of Electrical Engineering, Campus Tucuruí, UFPA. The bench multimeter project was developed using electrical signal conditioning circuits, selector switch to adjust the measurement scales, current sensors based on Hall effect, precision resistors, LCD display and atmega328p microcontroller for information processing. Simulations were performed in the Proteus 8.9 software, and measurements of resistance, DC current, DC voltage and power were performed. From the simulations, a printed circuit board project was proposed that could be manufactured to replicate the bench multimeter.